How Does Social Support Affect the Retention Willingness of Cross-Border E-Commerce Sellers? - Shen, Huiyun; Yu, Jie; Zhang, Hua; Gou, Jin; Zhang, Xiangqian (Frontiers in Psychology, 2022)
E-commerce research usually focuses more on how to protect consumers’ rights and increase their purchase intention from the perspective of consumers. However, we still lack understanding of e-commerce sellers, especially cross-border e-commerce sellers. Based on the stimulus-body-response theory, this paper built a moderated mediation model to test the relationships among social support, perceived benefits, perceived usefulness and sellers’ willingness to retain. The results show that social support has a positive impact on perceived benefits and sellers’ willingness to retain; perceived benefits play a partial intermediary role between social support and sellers’ willingness to retain; and perceived usefulness moderates these mediating effects. The research results further expand the perspective of e-commerce research and reveal the mechanism and boundary conditions of the influence of social support on the retention willingness of cross-border e-commerce sellers.